Interative method of calculation of originally circular-symmetric structures = Iteracyjna metoda obliczania modyfikowanych konstrukcji pierwotnie kołowo-symetrycznych - Pryputniewicz, Stanisław; Pryputniewicz, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper proposes an iterative method of calculation of modified, originally circular-symmetric structures. The method applies a cyclical (or quasi-cyclical) stiffness matrix of the original structure in each iteration step. A lot of modified systems which differ considerably from circular-symmetric ones (lack of some elements, strengthening, additional supports) have been calculated. The obtained results indicate that although the algorithm is not unconditionally convergent, exact solutions are often received even for considerable changes in the original structure. Operations on considerably smaller matrices than the full ones describing a system completely, compensate for the necessity of performing a greater number of iterations than when applying other methods of modification.
Keywords: mechanika konstrukcji; konstrukcje modyfikowane; circular-symmetric structures; modification; cyclic matrices